Winter cover crops in soybean monoculture: effects on soil organic carbon and its fractions - Duval, Matias Ezequiel; Galantini, Juan Alberto; Capurro, Julia Ester; Martinez, Juan Manuel (2018)
The current agricultural production systems in the Pampas Region have been significantly simplified by cultivating large land areas under no tillage (NT), where soybean is the predominant crop. These systems with long periods of fall-winter fallow and poor annual input of carbon (C) into the soil lead to soil degradation, thereby affecting physical and chemical properties. A 6-year cover crop study was carried out on a Typic Argiudoll under NT in the south of Santa Fe, Argentina. Various winter species were used as cover crops: wheat (W), oat (O), vetch (V), an oat + vetch mixture (O + V) and a control (Ct) treatment without a cover crop. We examined the influence of cover crops on the following soil organic C-fractions: coarse particulate organic carbon (POCc), fine particulate organic carbon (POCf) and mineral-associated organic carbon (MOC) from 2008 to 2011. Aboveground carbon input by the cover crops was related to the June to October rainfalls. In general, the W and O treatments supplied a higher amount of C to the soil; these gramineous species produced 22 and 86% more biomass than O + V and V. The water cost of including cover crops ranged from 13 to 93 mm compared with Ct. However, this water-use did not affect soybean yields. On average, gramineous species (pure stand or mixture) supplied more than 3.0 Mg C ha−1 year−1 to the soil, whereas V supplied less than 2.0 Mg C ha−1 year−1. Increase in the mean annual C-input by residues into the soil (cover crop + soybean) explained most SOC variation (R2 = 0.61; p < 0.05). This relationship was more evident with labile soil organic fractions, both for POCc (R2 = 0.91; p < 0.001) and POCc + POCf (R2 = 0.81; p < 0.001). The stratification ratios of SOC (SI, 0–5:10–20 cm) reflected differences among treatments, where >2.0 for W; 1.7 for O, O + V and V, and <1.5 for Ct. Soil physical fractionation by particle size showed that cover crops affected the most dynamic fraction directly associated with residue input (POCc) at 0–5 and 5–10 cm. At 0–5 cm, the effects were observed in the most transformed fractions (MOC and POCf) 4 years after the experiment started, whereas at 0–20 cm, differences in the labile fractions (POCc and POCf) were found at the end of the experiment (6 years). Although C-input by the cover crops fueled decomposition of labile soil organic fractions, concentration of surface SOC and its associated fractions (POCc, POCf and MOC) was modified after 6 years. This effect became noticeable during the third year when the plots under cover crops showed a higher SI than the traditional fallow.